ENT 530 Social Media Portfolio: Mirrorme / Lidiya Safura Shahrel Amir - Shahrel Amir, Lidiya Safura (2021)
Mirrorme’s headquarter is located at Kota Damansara, Selangor Darul Ehsan. The business is owned by myself, Lidiya Safura Binti Shahrel Amir, and also by a number of main partners, such as my mother, my sisters and my father as it is a family business. Mirrorme is a growing company that strives to acquire as much expertise as we can in the glass and mirror market industry. Our company needs more knowledge and understanding about business that can help us to indicate our weakness so that we can make change in order to meet future needs. The management of Mirrorme consists of co-owners my sister, Liyana Syahirah. The partner will be taking hands-on management the roles in the company business. Moreover, my youngest sister managing the marketing operation. Furthermore, we have assembled a board of advisors to provide management expertise. The advisors are, Puan Liza Abu Bakar which is my mother and my father Encik Shahrel Amir